Analisis Pengaruh Tingkat Pendidikan terhadap Kemiskinan di Indonesia Periode 2015-2021 - Sinarta Putra P. Surbakti; Masruri Muchtar; Pardomuan Robinson Sihombing (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2023)
This research aims to know the effect of education level on poverty in Indonesia for the 2015-2021 period. The study was conducted using a panel data regression random effect model. The results showed that the level of education indicated by the average length of schooling, literacy rate, and the number of poor people in the previous year simultaneously affected the number of poor people. Separately (partially), literacy rates have an inversely (negative) effect on the number of poor people. Conversely, the average length of schooling has a direct (positive) effect on the number of poor people. Based on this research, the government is expected to focus on quality and effectiveness in the education system in Indonesia. Quality education can be achieved by equal distribution of primary-level schools and by improving teaching staff quality. The government can also encourage the improvement of the Sekolah Menengah Kejuruan (SMK) program, which provides applied knowledge and added economic power to its graduates.